Respuesta :
Answer:
the answer is -4
Step-by-step explanation:
-16-4g=6g-6g
+4 +4
you add the -4g to both sides by changeing it to positive
then you have -16=6g-2g
then you go to the right side of the equation and solve, 6-2 is 4 then you have
-16=4g then you divide on both sides
-16 divided by 4 is
-4
Answer:
[tex]\Huge \boxed{g=-4}[/tex]
Step-by-step explanation:
[tex]-16-4g=6g-6g[/tex]
Combining like terms.
[tex]-16-4g=0[/tex]
Adding 4g to both sides.
[tex]-16=4g[/tex]
Dividing both sides by 4.
[tex]-4=g[/tex]